Color grouping in space and time: evidence from negative color-based carryover effects in preview search. - Braithwaite, J; Humphreys, G; Hodsoll, J (2003)
Five experiments addressed the role of color grouping in preview search (D. G. Watson and G. W. Humphreys, 1997). Experiment 1 used opposite color ratios of distractors in preview and second search displays, creating equal numbers of distractors in each color group in the final display. There was selective slowing for new targets carrying the majority color of the old items. This effect held when there was no bias in the preview and only the second search set had an uneven color ratio (Experiment 2). In Experiment 3, participants had foreknowledge of the target color, and effects were shown over and above those due to color biases. Experiment 4 demonstrated negative color carryover even when previews changed color. Experiment 5 showed reduced color carryover effects when previews were presented more briefly. Collectively, the results provide evidence for inhibitory carryover effects in preview search based on feature grouping.